Analisis Perbandingan Kinerja Reksadana Syariah dan Konvensional Periode 2012-2014 - Purbaningrum, Woro; , Dr. Daryono Soebagyo, MEC; , Nurul Huda M. Ag (2016)
This study aims to find out about 1) The difference in the performance of mutual funds Islamic and conventional (as seen from the return and risk), 2) The difference in the performance of mutual funds Islamic and conventional (seen from Sharpe index and Treynor index), 3) The difference in the performance of mutual funds and conventional (seen Daei Jensen Alpha). The method used in this research method of comparison to the determined sample of researchers during the month of January 2012 to December 2014. The sample was kind of Islamic and conventional mutual funds best for last 3 years. Hypothesis testing is done by using different test independent sample t-test using the program Statistical Product and Service Solution (SPSS) ver. 17.0, while the data used is the Net Asset Value per Unit (NAV / Unit), Jakarta Islamic Index (JII) and the Composite Stock Price Index (CSPI) and the data on Interest Rate of Bank Indonesia (SBI) monthly 2012-2014. These results indicate that the performance of Islamic and conventional mutual funds do not differ significantly. In the business performance of Islamic mutual funds are not less favorable to conventional mutual funds, religious and more accountable, because according to Islamic principles. Keywords: Performance, mutual funds, risk and return, Sharpe index, Treynor index, Jensen's Alpha.